Synthesis of Stilbene-Fused 2'-hydroxychalcones and Flavanones - Akçok, İsmail; Çağır, Ali; Çağır, Ali (Elsevier Ltd., 2010)
Synthesis of stilbene-fused chalcones and flavanones were successfully completed. Molecules were designed in a way to mimic the structural features of both "stilbene and chalcones" or "stilbene and flavanones" at the same time, and synthesized by three steps. Heck reactions of 3-bromobenzaldehyde with styrene derivatives gave corresponding (E)-stilbenes, which were reacted with acetophenones to furnish stilbene-fused 2′-hydroxychalcones under basic conditions. Finally, intramolecular cyclization reactions were performed to produce stilbene-fused flavanones. © 2010 Elsevier Inc.
Keywords: Chalcone; Flavanone; Heck reaction; Michael addition; Stilbene